A la caza del oro blanco - Keating, Mark (Novelist) (Narrativas históricas Edhasa., 2015)
Sold by his father for four guineas, Patrick Devlin knows just how cheap life is in a world of slavery, violence and greed. Devlin is taken as a servant by Captain John Coxon of the Royal Navy, whose job in this uneasy peace time is to protect the stupendous wealth of the East India Trading Company.